The Freudian Exodus: Psychoanalysis and the Mosaic Legacy - Barnaby, Andrew, (Contemporary Psychoanalytic Studies ;, 2024)
The Freudian Exodus redefines the traumatic experience that Freud argued was the origin of Judaic monotheism, the murder of Moses. Focusing instead on the Babylonian Exile, the study explores a series of topics understood as the aftershocks of t